2012
DOI: 10.1007/s00404-012-2621-y
|View full text |Cite
|
Sign up to set email alerts
|

Cervical cancer cells induce apoptosis in TCD4+ lymphocytes through the secretion of TGF-β

Abstract: Cervical cancer cells secrete TGF-β that inhibits lymphocyte proliferation and induces apoptosis in CD4+, but not in CD8+ lymphocytes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 21 publications
1
9
1
Order By: Relevance
“…HPV 16 E7 protein is shown to block the ability of TGF-β to inhibit cell proliferation [ 47 ] suggesting an association of HPV-associated malignant transformation to the loss of responsiveness to the TGF-β-mediated growth inhibitory signal. Cervical cancer cells secrete high levels of TGF-β that inhibit tumor infiltration by apoptosing CD4 lymphocytes evading host immune system [ 17 ]. Moreover, high expression of TGF-β1 predicts poor prognosis in patients with stage Ib-II1 squamous cell carcinoma [ 48 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…HPV 16 E7 protein is shown to block the ability of TGF-β to inhibit cell proliferation [ 47 ] suggesting an association of HPV-associated malignant transformation to the loss of responsiveness to the TGF-β-mediated growth inhibitory signal. Cervical cancer cells secrete high levels of TGF-β that inhibit tumor infiltration by apoptosing CD4 lymphocytes evading host immune system [ 17 ]. Moreover, high expression of TGF-β1 predicts poor prognosis in patients with stage Ib-II1 squamous cell carcinoma [ 48 ].…”
Section: Discussionmentioning
confidence: 99%
“…There is a marked increase in the expression of TGF-β mRNA and protein in human cancers and high expression of TGF-β correlates with more advanced stages of malignancy and decreased survival [ 16 ]. Cervical cancer cells are known to secrete TGF-β [ 17 ], which is capable of augmenting intratumoral stroma and decreasing tumor infiltrate, enhancing tumor growth and metastasis while evading host’s immune system [ 18 ]. The pivotal role of TGF-β in promoting tumor progression suggests that the signaling pathway may be a good target for therapy of cancer [ 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…To the best of our knowledge, the TGF-β/SMAD signaling pathway plays a role in numerous types of cancers, including cervical cancer (15)(16)(17). The TGF-β/SMAD signaling pathway mediated by TGF-β1 is thought to be a key signaling pathway in the regulation of cell proliferation and induction of apoptosis (18).…”
Section: Introductionmentioning
confidence: 99%
“…The TGF-β/SMAD signaling pathway mediated by TGF-β1 is thought to be a key signaling pathway in the regulation of cell proliferation and induction of apoptosis (18). Previous research has revealed that the proliferation and invasion of cervical cancer may be inhibited by TGF-β1 (17). TGF-β binds to TGFBR1 resulting in phosphorylation of the carboxy-terminal serine residue of the SMAD intracellular messenger proteins, SMAD2 and SMAD3 (19).…”
Section: Introductionmentioning
confidence: 99%
“…Much of the effect of TGFβ occurs during T cell development in the thymus and lymph nodes 80 , but TGFβ can also have suppressive effects in the context of a tumor milleu 94 . For example, conditioned medium from cervical cancer cell lines decreases lymphocyte proliferation and causes apoptosis in CD4+ cells in a TGFβ- dependent manner in vitro 404 .…”
Section: Immune Interactionsmentioning
confidence: 99%